A Mixed-Methods Exploration of the Educational Climate and Safety Climate During the First Year of Clinical Practice in Ireland. (4th June 2019) - Lydon, Sinéad; Byrne, Dara; Vellinga, Akke; Walsh, Chloe; Madden, Caoimhe; Connolly, Fergal; O'Connor, Paul
Abstract : Purpose: Educational climate (EC) and safety climate (SC) are key determinants of residents' professional development. The goal of this study was to gather longitudinal EC data and data on perceptions of SC in residency, and provide data on practices related to perceptions of EC and SC, by identifying factors associated with, and changes in, perceptions of EC and SC across the first year of practice and elucidating good and poor practice relating to key elements of EC and SC. Method: A mixed-methods design was adopted. First, 131 first-year residents in Ireland were surveyed at the end of each of their first three rotations (August 2016–March 2017). The survey measured EC using established measures. Next, 69 semistructured interviews were conducted with a representative sample of residents (March–May 2017). An interview schedule was developed to aid in-depth probing of EC and SC perceptions. Interviews were audio recorded, transcribed, and a deductive content analysis approach was adopted. Results: Perceptions of EC worsened over time. The EC and SC of surgical rotations were significantly poorer than those of medical rotations. Residents were more likely to describe team practices, rather than organizational practices, that contributed positively to their perceptions of EC and SC. Conclusions: Further research is necessary to facilitate improvement of EC and SC for residents, particularly within surgical training. Future research exploring the contribution of organizational practices to EC and SC, the impact of targeted improvement activities, and best practice for involving residents in quality and safety initiatives is recommended.